2020
DOI: 10.1200/jop.19.00221
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making About Genetic Testing Among Women With a Personal and Family History of Breast Cancer

Abstract: PURPOSE: To understand genetic testing use and decision making among patients with high genetic risk. MATERIALS AND METHODS: A survey of breast cancer survivors was administered online by a hereditary cancer nonprofit organization, Facing Our Risk of Cancer Empowered, from October 2017 to March 2018. RESULTS: Of 1,322 respondents, 46% had breast cancer at age < 45 years, 61% had a first-degree relative with cancer, and 84% underwent genetic testing, of whom 56% had a risk-associated pathogenic variant. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
(45 reference statements)
3
14
0
Order By: Relevance
“…Our study sought to explore and characterize the uncertainty experienced by carriers of pathogenic variants in the moderate-risk cancer genes ATM and CHEK2, drawing on Han's taxonomy of uncertainty. Consistent with other literature [33][34][35], our study found that participants undergo genetic testing because they expect that genetic test results will provide clarification regarding their cancer risks and clear recommendations on how to manage these risks. However, current scientific knowledge for genes such as ATM and CHEK2 may not actually lead to such clarification or recommendations.…”
Section: Discussionsupporting
confidence: 88%
“…Our study sought to explore and characterize the uncertainty experienced by carriers of pathogenic variants in the moderate-risk cancer genes ATM and CHEK2, drawing on Han's taxonomy of uncertainty. Consistent with other literature [33][34][35], our study found that participants undergo genetic testing because they expect that genetic test results will provide clarification regarding their cancer risks and clear recommendations on how to manage these risks. However, current scientific knowledge for genes such as ATM and CHEK2 may not actually lead to such clarification or recommendations.…”
Section: Discussionsupporting
confidence: 88%
“…Second-degree family history includes grandparents, aunts, uncles, grandchildren, nieces, nephews, and half siblings. Family history can identify individuals who should be referred for genetic counseling and testing, which causes considerable anxiety in women [ 13 , 14 , 15 ]. Women with a family history of breast cancer can overcome psychological distress by receiving appropriate supportive counselling [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study has several strengths including being the first registry-based study to systematically compare associations between socioeconomic and clinical factors and access to GHP among an ethnically and racially diverse sample of young breast cancer survivors treated across multiple healthcare settings, enhancing the generalizability of our findings. Furthermore, our estimates of provider discussion and genetic testing across diverse populations provides updated and novel data, compared to prior efforts with more limited minority representation 32 , 36 , 37 or older cohorts. 31 , 38 Despite these strengths, there remain some limitations, including that although participants were diagnosed within the same four years and eligibility criteria were the same, the Blacks and non-Blacks were recruited under separate protocols, which could contribute to recall bias across populations.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-test GC through a GHP has also been associated with increased recall about the implications of testing and the laws in place to prohibit insurance companies from denying coverage on the basis of the genetic test result. 36 Consequently, with expansion of gene-based care for those at risk for inherited cancer, these gaps highlight the need to standardize the delivery of pre-test GC to improve care across diverse populations and healthcare settings.…”
Section: Discussionmentioning
confidence: 99%